Aluminum zinc oxide nanostructures with customized size and shape by non-aqueous synthesis1. Issue 36 (28th September 2015) - Zellmer, S.; Kockmann, A.; Dosch, I.; Temel, B.; Garnweitner, G.
<x xml:space="preserve">Abstract</x> Aluminum-doped zinc oxide (AZO) nanocrystals with high crystallinity and tailored morphology ranging between spherical and rod-like were obtained by non-aqueous reaction at moderate temperatures.